Factors associated with the quality of caregivers interaction with children under 5 years old in Yogyakarta - Mungkasip Mungkasip; Fitri Haryanti; Akhmadi Akhmadi (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
The quality of caregiver and children under five interaction in YogyakartaPurposeThe purpose of this study was to determine factors related to the quality of caregiver interactions with children under five in Yogyakarta. MethodsThis study used a cross sectional design. Research subjects were all caregivers who have children aged 1.5 years to 4.5 years who have received cadre assistance in the work area of Mantrijeron Puskesmas Yogyakarta. Research subjects were recruited using total sampling techniques. The instrument used was questionnaire and PICCOLO observation sheet. Data analysis was done by Chi-Square test.ResultsThere was a significant correlation between knowledge factor and quality of domain interaction. There was no significant correlation between age factor, occupation, mental status, and income with interaction quality. ConclusionCaregivers are expected to improve the quality of interaction and communication with children, have sensitivity and responsiveness in practicing specific care, such as feeding, sensitivity to sick children, and able to develop each other's cognitive language.